Indonesia's Airspace Sovereignty and FIR Management with Singapore: Kedaulatan Wilayah Udara Indonesia dan Pengelolaan FIR dengan Singapura - Wahyudi, Andri; Chomariyah, Chomariyah; Dewanto, Wisnu Aryo (Indonesian Journal of Innovation Studies, 2025)
General Background: The delegation of Indonesia's Flight Information Region (FIR) over the Riau Islands and Natuna to Singapore has raised concerns about national sovereignty and international law. Specific Background: The Chicago Convention asserts that countries have complete sovereignty over their airspace, but Indonesia’s FIR management by Singapore challenges this principle. Knowledge Gap: The potential risks to sovereignty and security arising from this delegation have not been fully addressed. Aims: This study analyzes the implications of FIR delegation on Indonesia’s sovereignty and security, proposing steps for regaining control. Results: The study finds that Singapore's role is administrative, not a transfer of sovereignty, though it creates security risks. Novelty: The analysis offers new insights into the legal and strategic implications of FIR management. Implications: Recommendations focus on modernizing air navigation infrastructure and strengthening Indonesia's sovereignty. Highlights: Delegation of FIR to Singapore raises concerns over Indonesia's airspace sovereignty. The Chicago Convention ensures full sovereignty over airspace, yet the delegation remains an administrative issue. Regaining FIR control is crucial for Indonesia's national security and strategic interests. Keywords: FIR, Air Sovereignty, International Law, Security